2017
DOI: 10.4103/jcis.jcis_84_16
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Diffusion Coefficient Measurement in Mediastinal Lymphadenopathies: Differentiation between Benign and Malignant Lesions

Abstract: Objectives:We aimed to prospectively assess the diagnostic value of apparent diffusion coefficient (ADC) measurement in the differentiation of benign and malignant mediastinal lymphadenopathies.Materials and Methods:The study included 63 consecutive patients (28 women, 35 men; mean age 59.3 years) with 125 mediastinal lymphadenopathies. Echoplanar diffusion-weighted magnetic resonance imaging of the mediastinum was performed with b-factors of 0 and 600 mm2/s before mediastinoscopy and mediastinotomy, and ADC v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
0
0
6
Order By: Relevance
“…These are also similar to the results of Ustabasioglu F.E. et al [17], Nakayama J. et al [18], and Kosucu P. et al [19], who reported that the mean ADC value in malignant lymph nodes is low, with mean (1.030 ± 0.245 × 10 −3 mm 2 /s), (0.24 × 10 −3 mm 2 /s), and (1.012+/−0.025 × 10 −3 mm 2 /s) respectively.…”
Section: Discussionsupporting
confidence: 92%
“…These are also similar to the results of Ustabasioglu F.E. et al [17], Nakayama J. et al [18], and Kosucu P. et al [19], who reported that the mean ADC value in malignant lymph nodes is low, with mean (1.030 ± 0.245 × 10 −3 mm 2 /s), (0.24 × 10 −3 mm 2 /s), and (1.012+/−0.025 × 10 −3 mm 2 /s) respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Проведенное исследование показало высокую информативность ДВИ с оценкой ИКД лимфоузлов в дифференциальной диагностике МЛАП. В ряде аналогичных исследований также показаны значимые отличия ИКД при доброкачественных и злокачественных формах МЛАП [16][17][18]. Средние значения ИКД при злокачественной и доброкачественной МЛАП, по данным A.A. Razek et al, составили у взрослых 1,06 ± 0,3×10 −3 мм 2 /с и 2 , 3 9 ± 0 , 7 × 1 0 − 3 м м 2 / с [ 1 6 ] , у д е т е й -0,99 ± 0,18×10 −3 мм 2 /с и 1,35 ± 0,26×10 −3 мм 2 /с соответственно [17].…”
Section: результаты и обсуждениеunclassified
“…Эти же показатели в исследовании F.E. Ustabasioglu et al составили 1,03 ± 0,25×10 −3 мм 2 /с и 1,57 ± 0,56×10 −3 мм 2 /с [18]. Такой разброс значений ИКД при доброкачественной МЛАП в разных исследованиях может быть обусловлен разнородностью обследованных, различиями используемых параметров сканирования и способов сбора данных при получении ДВИ.…”
Section: результаты и обсуждениеunclassified
See 1 more Smart Citation
“…В настоящее время активно изучаются возможности ДВ-МРТ всего тела при лимфомах [12][13][14][15]. Ввиду ограниченного использования магнитнорезонансной томографии при патологии органов грудной клетки применению ДВ-МРТ в дифференциальной диагностике злокачественных и доброкачественных форм медиастинальной лимфаденопатии посвящено ограниченное количество работ [16][17][18][19].…”
unclassified